Tributação e concorrência: análise dos impactos de decisões judiciais em matéria tributária na livre concorrência - Rigotti, Thais Toledo (2023)
Taxes have an impact on the economic sphere and can generate distortions in competition between companies. As a result, judicial decisions on tax matters can also generate distortions of competition. The work aims to analyze what are the impacts of jurisdictional decisions on competition and how they happen. Thus, it starts with the analysis of market models and goes through the study of the principle of free competition and the constitutional economic order in order to understand how competition between companies works and is structured. Afterwards, the relations between the dispute and the competition are studied, evaluating which are the tax aspects that can influence the competitive order, as well as the reasons why this occurs. In the end, the effects that judicial decisions generated on free competition are studied, separating the analysis between decisions handed down inter partes and erga omnes. It is concluded that decisions binding only the parties involved in a given process do not a priori generate competitive impacts, while those with an erga omnes character can generate, requiring that the principle of free competition be considered in these judgments